Exploring FTAs, seafood exports, and SDGs: a gravity model analysis of Pakistan’s seafood trade with China and regional partners - Yuxiang Xia; Yuxiang Xia; Hengbin Yin; Hengbin Yin; Muhammad Mohsin; Ana Mehak; Cai Yan (Frontiers in Marine Science)
This study examines the effects of Free Trade Agreements (FTAs) on Pakistan’s seafood exports, specifically analyzing the China-Pakistan Free Trade Agreement (CP-FTA) and its stages, CP-FTAI and CP-FTAII. Using the gravity model (GM) of trade, it empirically analyzes the dynamics of seafood trade between Pakistan and its neighboring countries, aiming to provide insights into improving trade balance and export performance. The study employs three econometric approaches—Ordinary Least Squares (OLS), Fixed Effects Model (FEM), and Pseudo Poisson Maximum Likelihood (PPML) to ensure the robustness and reliability of the findings. The results reveal that Pakistan’s seafood exports are significantly influenced by FTAs, particularly with Afghanistan, Sri Lanka, and Malaysia, while CPFTA-I shows a positive impact. However, CPFTA-II exhibit negative and insignificant relationship, indicating that external shocks, like the COVID-19 pandemic, have impacted trade dynamics. The results of this study are significantly relevant to multiple United Nations Sustainable Development Goals (SDGs). Notably, they contribute to SDG 8, which focuses on Decent Work and Economic Growth, by promoting trade-driven economic advancement. Furthermore, they support SDG 9, which pertains to Industry, Innovation, and Infrastructure, by facilitating infrastructure development through the China-Pakistan Economic Corridor (CPEC). Additionally, they align with SDG 12, which emphasizes Responsible Consumption and Production by advocating sustainable trade practices. The study recommends enhancing FTAs, improving infrastructure, and expanding trade with neighboring markets to optimize Pakistan’s seafood export potential. Policymakers should focus on strengthening trade agreements, streamlining logistics, and integrating variables like security and exchange rates to develop more resilient and sustainable trade strategies, contributing to important SDGs.